PENERAPAN GOOD CORPORATE GOVERNANCE, DAMPAKNYA TERHADAP PREDIKSI FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI - Michell Ludy (Business Accounting Review, 2013)
This study aimed to know the impact of the implementation of Good Corporate Governance to the financial distress prediction. This study also used several control variables, namely Net Profit Margin, Debt to Asset Ratio, and Current Ratio. The samples used in this study were 31 companies in the sector of infrastructure, utilities, and transportation which listed in Indonesian Stock Exchange in the period of 2008-2011. The hypothesis was tested by using binary logistic regression. The results of this study proved that the Current Ratio was able to predict the company experienced financial distress in Model 1, while the other control variables were not able to predict. Model 2 proved that the Net Profit Margin Ratio was able to predict the company experienced financial distress, while the other control variables were not able to predict. Model 3 proved that the Good Corporate Governance Score, Net Profit Margin Ratio, Debt to Asset Ratio and Current Ratio were not able to predict the company experienced financial distress.